Fixed-bed column process as a strategy for separation and purification of Cephamycin C from fermented broth - Oliveira, Liliane M. (2015)
Fixed-bed column processes using the anionic resin Q Sepharose XL were evaluated for Cephamycin C (CepC) purification from fermentation broth. Breakthrough and desorption curves were obtained for different flow rates (2.5, 5.0 and 7.5 mL/min). The elution method consisted of a stepwise gradient using NaCl solutions (0.1, 0.3 and 0.5%), which resulted in the separation of CepC from others antibiotics. The flow rate did not interfere on adsorption during loading of the column, but band broadening was observed during elution as the flow rate increased. After the ion exchange process, the fractions containing CepC were submitted to solid phase extraction using a C18 cartridge to remove salts. Analyses of the broth used to feed the column and of the salt-free fractions by LC-MS showed a reduction in the concentration of some contaminants (possibly penicillin N, deacetylcephalosporin C, and deacetoxycephalosporin C) compared to the concentration of CepC. In conclusion, ion exchange process followed by adsorption on a C18 adsorbent was demonstrated to be a selective and efficient procedure to purify CepC from fermentation broth.